Skin and soft-tissue coverage for limb salvage in extensive diabetic foot ulcers: An institutional experience - Petkar, Kiran; Gourav Prasad (Asian Journal of Medical Sciences, 2023)
Background: Extensive diabetic foot ulcers (DFUs) with skin and soft-tissue defects need prompt coverage of the defect using plastic surgical means. The indication, timing, and techniques of wound coverage in DFUs are not adequately understood by all. Hence, an institutional experience of providing skin and soft-tissue coverage to extensive DFUs is reported. Aims and Objectives: The aims of this study were to study the various types of DFU that needs surgical wound coverage and to understand the types of wound coverage surgeries, their timings, success rates, and final outcomes. Materials and Methods: A retrospective-prospective study of all the DFUs managed using skin and soft-tissue coverage was conducted. Surgical and medical management and their outcomes were studied. Results: Sixteen patients underwent skin graft or flap surgery for their DFU. All the limbs were salvaged and all wounds were covered with two reports of ulcer recurrences. Conclusion: For optimal care of DFUs, the possible need for wound coverage, it’s timing, and aftercare are to be understood by all involved.